GFRP-brick strengthening systems under high strain rates - Pereira, João Miguel (2016)
Fibre Reinforced Polymers have become a popular material for strengthening of masonry structures. The performance of this technique is strongly dependent on the bond behaviour between the FRP and the substrate. Understanding the strain rate effect on the bond behaviour of this strengthening technique is important for proper design and proper modelling of these systems under impacts or blast loads. This work aims to study the bond behaviour between Glass Fibre Reinforced Polymers and brick at different strain rates. A Drop Weight Impact Machine specially developed for pull-off tests (single lap shear tests) is used with different masses and different heights introducing different deformation rates. The strain rate effect on the failure mode, shear capacity and effective bond length is determined from the experimental results. Empirical relations of dynamic increase factors for these materials and techniques are also presented.